Body Image Negatif Berdampak Pada Kecemasan Remaja Putri di Masa Pubertas: Literature Riview - Dumar, Bergita; Ida Wahyuni; Nur Fitriah Jumatrin; Mery Eka Yaya Fujianti (Universitas Nazhatut Thullab Al- Muafa Sampang, 2024)
Introduction: Adolescence is a transition period from childhood which results in many changes experienced in all aspects of life, such as physical and psychological aspects. Psychological and physical changes can influence negative Body Image in young women so that it can have an impact on emotional problems such as anxiety, the anxiety that arises can reduce the productivity of young women. Objective: This Literature Review aims to discuss negative Body Image related to anxiety in young women in puberty. Method: This study uses a literature review method to see how big the impact of negative body image is on the anxiety of young women during puberty. This literature uses references from the last 10 years (2014-2024) with titles that are relevant to the title raised. Results: The negative body image that occurs in this transition phase has quite a significant impact on the anxiety of young women during puberty. Conclusion: It can be concluded that anxiety in young women during puberty can be caused by a negative Body Image. Pendahuluan: Usia remaja menjadi masa peralihan dari masa kanak-kanak yang mengakibatkan banyaknya perubahan yang dialami dalam segala aspek kehidupannya seperti fisik dan aspek psikologis. Perubahan secara psikologis dan fisik dapat mempengaruhi Body Image negative pada remaja putri sehingga dapat berdampak pada masalah emosional seperti kecemasan, kecemasan yang muncul dapat mengurangi produktivas remaja putri.. Tujuan: Literature Riview ini bertujuan untuk membahas terkait Body Image negative terhadap kecemasan pada remaja putri di masa pubertas. Metode: Studi ini memakai metode literature review untuk melihat seberapa besar dampak yang ditimbulkan dari Body Image negatif pada kecemasan remaja putri di masa pubertas.Literature ini menggunakan referensi 10 tahun terakhir (2014-2024) dengan judul yang relevan dengan judul yang diangkat. Hasil: Body Image negatif yang terjadi difase transisi ini berdampak cukup signifikan terhadap kecemasan remaja putri dimasa pubertas.Kesimpulan: Dapat disimpulkan bahwa kecemasan pada remaja putri di masa pubertas dapat diakibatkan karena Body Image yang negative.